2013
DOI: 10.1007/s00464-013-3290-z
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery after endoscopic resection of malignant rectal polyps: a useful technique for indication to radical treatment

Abstract: Background Management of malignant rectal polyps (MRPs) after endoscopic polypectomy (EP) is still debated. It is sometimes difficult to decide whether to simply follow-up (FU) or to treat such a removed lesion. Transanal endoscopic microsurgery (TEM) could have a role both in T staging and in treating MRPs after EP. Methods Patients who underwent a full-thickness TEM within 3 months after an EP between January 2008 and October 2012 were retrospectively analyzed. If post-TEM histology showed locally advanced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
0
20
0
2
Order By: Relevance
“…Arolfo et al . also reported the need to perform a TME in four patients (14.9%). It has been shown that prior TEM does not jeopardize a subsequent TME in terms of oncological outcome if it is performed within 4–6 weeks .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Arolfo et al . also reported the need to perform a TME in four patients (14.9%). It has been shown that prior TEM does not jeopardize a subsequent TME in terms of oncological outcome if it is performed within 4–6 weeks .…”
Section: Discussionmentioning
confidence: 97%
“… Morphology and the level of invasion of adenocarcinoma in the polyp . In pedunculate polyps at Haggitt level 4 the risk of lymph node metastasis is 12%–25%, but it is below 1% at Haggitt levels 0–3 , and in sessile polyps the risk of lymphatic involvement is proportional to the degree of submucosal invasion, with rates of 1%–3% in Kikuchi sm1 polyps, 8% in sm2 and 23% in sm3 . Poor differentiation is associated with a 36%–38% likelihood of recurrence or residual lesions . Lymphovascular invasion is associated with a risk of persistence or relapse of 17%–39% . Resection margin : when the resection margin is below 1 mm or affected, the recurrence rate is 21%–33% compared with 0%–2% if the margin is above 1 mm . Tumour budding is an indicator of the aggressiveness of malignant polyps that is associated with a high risk of lymph node metastases, with an odds ratio of 7.74 (95% confidence interval) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die gesamte R0-Rate von Rektum und Kolon betrug 80 % bei einer erzielten Vollwandresektion in 60 % der Fälle. Die diagnostische Aussagekraft einer Vollwandresektion im Rektum mittels klassischer transanaler endoskopischer Mikrochirurgie (TEM) oder der "transanal minimal invasive surgery" (TA-MIS) ist einer endoskopischen Resektion (EMR, ESD) überlegen [8,9]. Darüber hinaus gelingt auch mit der ESD eine diagnostisch zu fordernde En-bloc-Resektion zu Rand und Tiefe nicht immer; die Ergebnisse schwanken zwischen 62-88 %, mit Perforations-und relevanten Blutungsraten von bis zu 14 bzw.…”
Section: Histologischer Resektionsbefundunclassified
“…The safety and efficacy of endoscopic resection means that TEMS is not appropriate for treatment of benign naive rectal polyps. It is likely that TEMS has a role for salvage treatment following failed endoscopic resection and it may have a role in select patients with T1 rectal cancer . Beyond the rectum, endoscopic full‐thickness resection (EFTR) is technically possible; however, major barriers exist in closure of a full thickness defect .…”
Section: Advanced Lesionsmentioning
confidence: 99%